The Impact of the Implementation of the Quick Response Indonesian Standard (QRIS) on Encouraging the Economic Growth of Micro, Small, and Medium Enterprises (MSMEs) in Jayapura Regency - Markus Setiawan Soumokil; Wilhelmina Anastasia I. Arfusau; Pisi Bethania Titalessy; Neni Setiarini; Mike S Tokoro; Lynn Ibo (Journal of International Conference Proceedings, 2025)
The results of this study indicate that the use of the QRIS payment system has a positive and significant effect on the economic development of MSMEs in Jayapura Regency. This can be interpreted to mean that the use of the QRIS payment system has a positive impact on increasing the income of MSMEs in Jayapura Regency (t-count value of 5.782 t-table value of 1.701, and a significance value for the QRIS payment system variable (X) of 0.000 0.05). Furthermore, based on statements from MSME respondents in Jayapura Regency who use QRIS, several constraints were identified, namely: some users still do not fully understand how to use QRIS, network connectivity issues, delays in real-time/instant fund disbursement, the existence of QRIS usage fees charged to merchants, and the absence of transaction fee discounts or promotions as offered by payment applications such as OVO, GoPay, and others. However, these constraints are perceived as not having a significant overall impact on their business income. This is evidenced by the fact that out of 30 respondents, only 19 respondents stated that these constraints did not significantly affect their business income.